Fruit formation dynamics in parthenocarpic cucumber (Cucumis sativus L.) in spring forcing - Helyes, L.; Pék, Z. (International Journal of Horticultural Science, 2004)
20% of the cucumber crop of the world belongs to the parthenocarp type. Parthenocarp cucumber forcing has a great importance in Hungary, too. In our country the whole area of parthenocarp cucumber forcing was approximately 500 ha of the last years (2000-2002) and 75-85000 tons of yield has been harvested (MGYSZT, 2003). It means 15 — 17 kg/m2 as an average yield. In European forcing systems, parthenocarp cucumber is usually planted in January or February and it is harvested in spring or early summer. In Hungary cucumber forcing is the most profitable in two separate periods: spring and autumn, the reason for it is the changes of the average prices of fresh market cucumber, but spring forcing is still the most profitable. Forced cucumber cultivars are mostly parthenocarp; non-parthenocarp cultivars are grown in summer preferably. Cucumber cultivars, forced in our country, are hybrids, and 90% of them are offered by foreign seed companies (KristOfne, 1998.). The productivity of these hybrids is high and the productive period is quite short. All the mentioned details give the reason why it is important to know everything about the productivity, the dynamics of growth, and the possibilities of timing of parthenocarp cultivars, and it is also important to learn how to control all these parameters. Our spring cucumber-forcing experiment aimed to characterize of those parameters mentioned.